Analisis Hukum Pidana Dalam Menangani Anak Jalanan Yang Melakukan Tindak Pidana Studi Kasus Di Kota Medan - Epandi Ashari; Shofia Riani; Mhd. Umar Harahap (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2025)
This article discusses the analysis of criminal law in dealing with street children involved in criminal acts, focusing on a case study in Medan City. With the increasing number of street children and the complexity of the social problems they face, this study aims to explore how the criminal law system in Indonesia functions in the context of child protection. The method used is a qualitative approach with descriptive analysis of data obtained through interviews, legal documents, and field observations. The results of the study indicate that although there are regulations governing child protection, their implementation is often hampered by a lack of coordination between related institutions and social stigma against street children. In addition, a legal approach that is too repressive tends to be ineffective in rehabilitating these children. This study suggests the need for integration between legal, social, and educational approaches to create an environment that supports the reintegration of street children into society.